Less-tight versus tight control of hypertension in pregnancy - Magee, Laura A.; von Dadelszen, Peter; Rey, Evelyne; Ross, Susan; Asztalos, Elizabeth; Murphy, Kellie E.; Menzies, Jennifer; Sanchez, Johanna; Singer, Joel; Gafni, Amiram; Gruslin, Andrée; Helewa, Michael; et al. (Massachusetts Medical Society, 2015)
BACKGROUND The effects of less-tight versus tight control of hypertension on pregnancy complications are unclear. METHODS We performed an open, international, multicenter trial involving women at 14 weeks 0 days to 33 weeks 6 days of gestation who had nonproteinuric preexisting or gestational hypertension, office diastolic blood pressure of 90 to 105 mm Hg (or 85 to 105 mm Hg if the woman was taking antihypertensive medications), and a live fetus. Women were randomly assigned to less-tight control (target diastolic blood pressure, 100 mm Hg) or tight control (target diastolic blood pressure, 85 mm Hg). The composite primary outcome was pregnancy loss or high-level neonatal care for more than 48 hours during the first 28 postnatal days. The secondary outcome was serious maternal complications occurring up to 6 weeks post partum or until hospital discharge, whichever was later. RESULTS Included in the analysis were 987 women; 74.6% had preexisting hypertension. The primary-outcome rates were similar among 493 women assigned to less-tight control and 488 women assigned to tight control (31.4% and 30.7%, respectively; adjusted odds ratio, 1.02; 95% confidence interval [CI], 0.77 to 1.35), as were the rates of serious maternal complications (3.7% and 2.0%, respectively; adjusted odds ratio, 1.74; 95% CI, 0.79 to 3.84), despite a mean diastolic blood pressure that was higher in the less-tight-control group by 4.6 mm Hg (95% CI, 3.7 to 5.4). Severe hypertension (≥160/110 mm Hg) developed in 40.6% of the women in the less-tight-control group and 27.5% of the women in the tight-control group (P<0.001). CONCLUSIONS We found no significant between-group differences in the risk of pregnancy loss, high-level neonatal care, or overall maternal complications, although less-tight control was associated with a significantly higher frequency of severe maternal hypertension. (Funded by the Canadian Institutes of Health Research; CHIPS Current Controlled Trials number, ISRCTN71416914; ClinicalTrials.gov number, NCT01192412.)